ANTIHYPERGLYCEMIC, ANTIOXIDANT, AND ANTIHYPERLIPIDEMIC ACTIVITIES OF EXTRACT FROM COCCINIA GRANDIS (L.) VOIGT. LEAVES BY METHANOL ON ALLOXAN INDUCED HYPERGLYCEMIC MICE - Xuan Trang, Dai Thi; Linh, Vo Chi; Ai Lan, Nguyen Thi (Vietnam Journal of Biotechnology, 2018)
The aim of this study was to investigate antihyperglycemic, antihyperlipidemic and antioxidant activities of the extract of Coccinia grandis leaves (CGL) by methanol in alloxan induced diabetic mice. Hyperglycemic was induced in mice by administration of alloxan monohydrate (135 mg/kg, ip.). CGL was orally given to the normal mice (100 and 1000 mg/kg body weight) to determine the toxicity of CGL. Hyperglycemic mice were treated with the extract of CGL (100 mg/kg body weight/ twice a day). Glucophage, diabetic commercially available drug, was used as a possitive control with dose of 108 mg/kg body weight/twice a day. Mice were administered with both glucophage and CGL extract orally during 21 days. On the 21st day of the experiment, mice blood, liver and brain samples were collected to test biochemical parameters and antioxidant levels. CGL did not show toxicity and death up to dose 1000 mg/kg in mice. Administration of CGL 100 mg/kg significantly (p<0.05) reduced blood glucose levels in alloxan induced hyperglycemic mice. Besides, several serum lipid values including total cholecterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C) reduced while high density lipoprotein cholesterol (HDL-C) increased. Malondialdehyde (MDA) in a group of untreated hyperglycemic mice was statistically higher than that of nomal mice. The MDA levels of livers and brains in the CGL treated hyperglycemic mice were lower than that of hyperglycemic control. The effects of hypoglycemic, antihyperlipidemic and antioxidant of CGL were higher than that of glucophage. The total polyphenols and flavonoids contents of the leaf extract were 607,41 + 14,44 mg gallic acid or quercetin equivalents/g and 111,72 + 1,94 mg equivalents/g, respectively. In conclusion, the antihyperglycemic, antihyperlipidemic and antioxidant effects of the CGL suggest a potential therapeutic treatment for hyperglycemic conditions.